Character Strengths Across Disabilities: An International Exploratory Study and Implications for Positive Psychiatry and Psychology - Umucu, Emre; Lee, Beatrice; Genova, Helen M.; Chopik, William J.; Sung, Connie; Yasuoka, Mizuka; Niemiec, Ryan M. (Frontiers in Psychiatry, 2022)
The purpose of this exploratory study was to examine the differences in character strengths for people with disabilities by using an international dataset by the VIA Institiute on Character. Specifically, we aimed to explore (a) the top and bottom five character strengths reported by different disability groups and all people with disabilities more broadly, and (b) group differences in each character strength and total character strengths. The investigator contacted the VIA Institute on Character (http://www.viacharacter.org/) for obtaining the dataset for the current study. After data cleaning, our sample size resulted in 11,699 people with disabilities. Among most people with disabilities, the top five character strengths scores were love of learning, honesty, appreciation of beauty and excellence, kindness, and fairness. The bottom five character strengths scores were self-regulation, perseverance, zest, spirituality, and prudence. Knowing that there is heterogeneity in character strengths across groups gives us a better understanding of the areas that people with different disabilities and conditions might thrive and provides clinicians and practitioners with a more nuanced understanding for how to possibly intervene with their clients. Positive psychiatry and psychology implications are discussed.